Nitrogen isotope systematics and origins of mixed-habit diamonds. (15th May 2015) - Howell, D.; Stern, R.A.; Griffin, W.L.; Southworth, R.; Mikhail, S.; Stachel, T.
Abstract: Nitrogen isotope values from mantle diamonds are a commonly used tracer in the quest to track volatiles within the Earth's mantle through deep time. Interpretations of this isotope data are valid so long as stable isotope fractionation processes in the mantle are understood. The fractionation of nitrogen isotopes between {1 1 1} and {1 0 0} growth sectors is well documented for high-pressure high-temperature (HPHT) synthetic diamonds, but there is little data on whether it also occurs in natural mixed-habit diamonds. We present 91 in-situ nitrogen isotope (δ 15 N) measurements, along with carbon isotope (δ 13 C) values and nitrogen abundances [N], obtained from three mixed-habit diamonds by secondary ion mass spectrometry (SIMS). While the well-documented enrichment of nitrogen concentrations in octahedral sectors compared to contemporaneous cuboid sectors is observed, a similarly clear disparity is not obvious in the δ 15 N data. Whereas HPHT synthetic diamonds exhibit 15 N enrichment in the {1 0 0} sectors by ∼+30‰, the mixed-habit diamonds studied here show enrichment of the octahedral sectors in 15 N by only 0.4–1‰. This major difference between HPHT synthetic and natural mixed-habit diamonds is proposed to be the result of different physical properties of the growth interfaces. The smooth interfaces of the octahedral sectors are the same in both types of crystal, but the outermost atoms on the smooth cube interfaces of an HPHT synthetic diamond behave differently to those on the rough cuboid interfaces of the natural mixed-habit diamonds, resulting in different δ 15 N values. Both the δ 13 C (average of ∼−8.7‰) and δ 15 N (average of ∼0‰) data show only minor offsets from the typical mantle values (δ 13 C = −5 ± 3‰, δ 15 N = −5 ± 4‰). This may indicate diamond formation from a mantle derived fluid/melt containing a minor subducted component (lowering δ 13 C values and elevating δ 15 N) or relate to moderate degrees of isotopic fractionation of a pure mantle fluid/melt by prior diamond precipitation. The homogeneous nature of both the carbon and nitrogen isotopic compositions of all three diamonds, however, documents continuous and unlimited supply of diamond forming fluid/melt, with a constant composition. Such homogenous isotopic compositions exclude fluid mixing or isotopic fractionation close to the site of diamond formation and preclude distinguishing between these two processes based on diamond analyses alone.